Effect of Nutrient Management on Soil Fertility and Productivity under SRI Method of Cultivation - Alok Kumar and S.F.A. Zaidi, Suresh Kumar, S.K. Tiwari (Journal of the Indian Society of Soil Science, 2016)
A field study was conducted at the Instructional Farm of Narendra Deva University of Agriculture and Technology, Kumarganj, Faizabad (Uttar Pradesh) during kharif, 2012 to evaluate the effect of integration of nitrogen (N) management in rice under SRI (system of rice intensification) method. Seven N management combinations were evaluated in a randomized block design. Growth parameters, yield attributes and grain yield (6.43 t ha-1) were increased significantly with the application of 75% N through fertilizer + 25% N through green manuring (Sesbania) over T5 (50% N through fertilizer + 25% N through FYM + 25% N through green manuring), T6 (50% N through fertilizer + 50% N through FYM), T7 (100% N through FYM) and T1 (Control), and statistically at par with T2 (100% N through fertilizer) and T3 (75% N through fertilizer + 25% N through FYM). The maximum uptake of N (123 kg ha-1), phosphorus (37.1 kg ha-1) and potassium (152 kg ha-1) was also recorded with the treatment having 75% N through fertilizer + 25% N through green manuring and minimum with T1 (Control). Also, the maximum income (Rs. 61358 ha-1) and benefit:cost ratio (1.92) were obtained with this treatment.